(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Participating in sport and physical activity provides multiple benefits for physical and mental health, and for quality of life. However, women and girls have long been an underrepresented group in sport, as participants, leaders, coaches, officials, administrators, athletes, and in the media (Cooky et al., 2021; Leabeater et al., 2023). In Ireland, a new all-island consortium has been established to conduct high-quality interdisciplinary research focused on women and girls in sport. It aims to understand, intervene on, and ultimately improve the health, wellbeing, participation, and performance of women and girls in and through sport, exercise, and physical activity. Our mission is that working together with practitioners, policymakers, and academics will help drive meaningful change for women and girls in and through sport, exercise, and physical activity. This symposium will provide insights into the process of establishing a sustainable consortium of interdisciplinary researchers in the area of women in sport, and the benefits for policy, advocacy, and practical action. The symposium starts with an overview of the building of míde. The second presentation provides a perspective from a recent scoping review of research about women in sport from the island of Ireland. The third presentation provides an example of how to ensure the voices of participants are heard in project design. Finally, the symposium will conclude with a critical reflection on the importance of male allyship, and a discussion amongst participants on the potential to scale out míde activities in Europe.